2018
DOI: 10.1002/chem.201804656
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Induced Alkyne Cycloisomerization: Construction of Metalated Heterocycles, Revelation of Unconventional Reaction Pathways, and Exploration of Functional Applications

Abstract: While the fascinating chemistry demonstrated by metalated N-heterocyclic carbene( NHC) complexes highlights the significance of metalated heterocyclic chemistry,t he development of other metalatedh eterocycles is falling behind, presumably because of the sparseness of general synthetic methodologies. In this Concept article, the strategy to preparem etalated heterocyclic complexes by metal-inducedc ycloisomerization of heteroatom-functionalized alkynes is presented. The isolation of and calculations on novel r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Given that cyclization of alkynesr epresents one of the most general approaches to prepareh eterocycles, together with the recentf indings that activation of alkynes by Ru II precursors is an effective strategy to prepare metalated heterocyclic complexes for druga nd material discoveries, [34] Ru-induced alkyne cyclization is expected to attract considerable interesti nt he field. As evident from the studies summarized in this Minireview,t he vinylidenei ntermediacy should not be taken for granted regarding the mechanism in any Ru-mediated alkyne transformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that cyclization of alkynesr epresents one of the most general approaches to prepareh eterocycles, together with the recentf indings that activation of alkynes by Ru II precursors is an effective strategy to prepare metalated heterocyclic complexes for druga nd material discoveries, [34] Ru-induced alkyne cyclization is expected to attract considerable interesti nt he field. As evident from the studies summarized in this Minireview,t he vinylidenei ntermediacy should not be taken for granted regarding the mechanism in any Ru-mediated alkyne transformations.…”
Section: Discussionmentioning
confidence: 99%
“…Around the same time, Wong and co-workers initiated a project to synthesize metalated heterocyclic complexes through metal-induced cycloisomerization of heteroatom-func-tionalized alkynes, [34] and isolated some Ru-heterocyclic complexesa rising from the "non-vinylidene-involving" pathways. In 2013 and 2014, they isolated Ru-indolizinec omplexes 7 from the reactions between pyridine-substituted propargylic alcohols HCCC(OH)(2-py)R (S7)a nd Ru II precursors [Ru([9]-aneS3)(bpy)(OH 2 )] 2+ + and [Ru( [14]aneS4)Cl 2 ]( Scheme 23; [9]aneS3 = 1,4,7-trithiacyclononane, [14]aneS4 = 1,4,8,11-tetrathiacyclotetradecane).…”
Section: Catalytic Ru II -Mediated Cyclizations Of N/o-functionalizedmentioning
confidence: 99%
“…Recently, we have been scrutinizing the reactivity between structurally well‐defined low‐valent transition‐metal complexes and functionalized alkynes, and several classes of interesting and unprecedented metal‐heterocyclic and metallacyclic complexes were isolated . We herein report a series of phosphonium‐bearing bicyclic ruthenafuran and osmafuran complexes prepared from the reactions between cis ‐[Ru/Os(dppm) 2 Cl 2 ] and terminal ynones HC≡C(C=O)R. DFT calculations revealed that the metal‐vinylidene‐involving pathway represents an energetically feasible formation mechanism for these complexes.…”
Section: Methodsmentioning
confidence: 99%
“…[8] To date, the exploration of synthetic approaches that enable the preparation of novel metallafurans remains unabated.Recently,w ehave been scrutinizing the reactivity between structurally well-defined low-valent transition-metal complexes and functionalized alkynes, and several classes of interesting and unprecedented metal-heterocyclic and metallacyclic complexesw ere isolated. [9, 10] We herein report as eries of phosphonium-bearing bicyclicr uthenafuran and osmafuran complexes prepared from the reactions between cis-[Ru/Os(dppm) 2 Cl 2 ] and terminaly nonesH C C(C=O)R. DFT calculationsr evealed that the metal-vinylidene-involving pathway represents an energetically feasible formation mechanism for these complexes. Interestingly,t he metallafurans exhibit stronger cytotoxicity against several human cancer cell lines in comparison with their metal precursors and the classica nticancer drugc isplatin, and have shown ability to induce mitochondrial dysfunction in cells.Phosphonium ring-fused bicyclic metallafuran complexes 1(PF 6 )a nd 2(PF 6 )w ere prepared from reactions between cis-[M(dppm) 2 Cl 2 ]( racemic;o nly one enantiomer is shown in the schemes and figures) and terminal ynones HCC(C=O)R in the presence of NaPF 6 in CH 2 Cl 2 (Scheme 1), during whicht he reaction mixturest urned from yellowishb rown to deep purple.…”
mentioning
confidence: 99%
“…Our group has recently initiated a paradigm in scrutinizing the reactivity between low-valent transition metal precursors and heteroatom-functionalized alkynes [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Gratifyingly, several Ru-and Os-heterocyclic complexes reported by our group exhibit interesting biological applications.…”
Section: Introductionmentioning
confidence: 99%